Stiff fluid spike solutions from Bianchi type V seed solutions. (15th November 2017) - Gregoris, D; Lim, W C; Coley, A A
Abstract: In this paper we expand upon our previous work Coley et al (2016 Class. Quantum Grav .33 215010) by using the entire family of Bianchi type V stiff fluid solutions as seed solutions of the Stephani transformation. Among the new exact solutions generated, we observe a number of important physical phenomena. The most interesting phenomenon is exact solutions with intersecting spikes. Other interesting phenomena are solutions with saddle states and a close-to-FL epoch.